2016
DOI: 10.2460/javma.248.11.1267
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of malignancy and outcomes for dogs undergoing splenectomy for incidentally detected nonruptured splenic nodules or masses: 105 cases (2009–2013)

Abstract: OBJECTIVE To determine the frequency of malignancy and survival rates of dogs that underwent splenectomy for incidentally detected nonruptured splenic masses or nodules. DESIGN Retrospective case series. ANIMALS 105 client-owned dogs. PROCEDURES Medical records of dogs that underwent splenectomy at a veterinary teaching hospital between 2009 and 2013 were examined to identify patients with incidentally detected nonruptured splenic masses or nodules without associated hemoperitoneum. Only dogs with histological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 16 publications
6
35
0
Order By: Relevance
“…processes [ 1 4 ]. Hemangiosarcoma has been reported by some researchers as the most common splenic mass in dogs [ 1 , 5 ]; however, others have reported higher prevalence of benign lesions [ 2 – 4 ]. In contrast, the prevalence of benign versus malignant lesions has been well established in dogs with non-traumatic hemoabdomens.…”
Section: Introductionmentioning
confidence: 99%
“…processes [ 1 4 ]. Hemangiosarcoma has been reported by some researchers as the most common splenic mass in dogs [ 1 , 5 ]; however, others have reported higher prevalence of benign lesions [ 2 – 4 ]. In contrast, the prevalence of benign versus malignant lesions has been well established in dogs with non-traumatic hemoabdomens.…”
Section: Introductionmentioning
confidence: 99%
“…The ratio of non‐neoplastic to neoplastic splenic disease in dogs varies among previous studies. Studies that included all cases of splenomegaly or masses showed >50% prevalence of non‐neoplastic diseases …”
Section: Discussionmentioning
confidence: 99%
“…Sonographically detected splenic parenchymal changes can be found during abdominal ultrasound examination in asymptomatic patients or patients with unrelated disorders. Splenic nodules without associated splenomegaly are a relatively common finding in older dogs, are likely to be benign, and may require no further action in this age group . Nodular hyperplasia, hematoma, extramedullary hematopoiesis, congestion, and lymphoid hyperplasia are the most common non‐neoplastic lesions found in the spleen of dogs at necropsy or on biopsy, whereas the most common malignant neoplastic lesions of the spleen in dogs are hemangiosarcoma, histiocytic sarcoma, non‐angiomatous or nonlymphoid sarcomas, and lymphoma .…”
Section: Introductionmentioning
confidence: 99%
“…However, in this case, despite the large mass dimensions, this complication did not occur. Studies indicate that hemangiosarcoma is more susceptible to rupture and bleeding prior to diagnosis when compared with other malignant splenic neoplasms (Spangler et al, 1994;Cleveland and Casale, 2016;Sherwood et al, 2016).…”
Section: Discussionmentioning
confidence: 99%